An analysis of seal integrity of vials used in biotechnology companies - Muñoz González, Edisbel (2021)
The research objective was to characterize the seal integrity of vials used for pharmaceutical products as a basis for an operational reliability analysis. The vial/stopper/seal height measuring method, experimental methods and expert evaluations were used. The main result was the technical characterization of the vial capping process, as well as the determination of its working parameters and ranges.